Design of an Automatic Water Faucet System Using the IOT Based HC-SR04 Sensor - Sinaga, Rio; Novriyenni, Novriyenni; Syahputra, Siswan (Yayasan Kita Menulis, 2023)
Water is a vital element for humans, many activities are related to water. In everyday life, the use of water becomes very important and necessary in various fields, such as households, industry and agriculture. But their use is often inefficient and has the potential to waste valuable resources. In this context, the concept of the Internet of Things (IoT) emerges as a potential solution by connecting physical objects via the internet. This research designs and builds an IoT-based automatic water faucet system using the HC-SR04 sensor to measure the water level in a container. Hardware components such as Node mcu Esp8266, Infrared Sensor, 2 channel 5v Relay, and others are used to control the system automatically. The software used includes the Arduino IDE. This system aims to intelligently monitor and control water flow, prevent water wastage, and incorporate the advantages of IoT technology to create an automatic water faucet system that is responsive to water levels and the presence of objects in front of it.